Exploring the Role of Restorative Justice in the Recovery of State Finances from Corruption Crimes - Nurhayati Mardin; Lestari Wulandari S; Adiguna Kharismawan (Faculty of Law, Universitas Pekalongan, 2025)
This article delves into the essence resonating with Indonesia's values, embodying a distinctive manifestation of retributive justice rooted in classical criminal law. Employing the juridical normative method, we explore the compatibility of the Restorative Justice program with Indonesian law and Pancasila principles, specifically addressing financial fraud. Positioned as a national policy, Restorative Justice posits that economic emulation requires holistic support, emphasizing the social impact of punishment as a deterrent and preventive measure. The implementation calls for a nuanced, humane approach outlined in the RKUHP's Ius Constituendum to effectively achieve its goals of prevention and intervention. This study proposes a compelling strategy, urging the public admission of guilt as a moral responsibility to counteract corruption's detrimental effects, aligning with the theme